Development of e-governance in Ukraine based on the concept of m-governance - SVITLANA, LEVCHENKO; ALLA, KOZHYNA; VIKTORIYA, IVANYUTA; IRYNA, KRAVETS; MARYNA, SHASHYNA (The journal of contemporary issues in business and government, 2020)
Technological solutions within the concept of m-governance accelerate the provision of public services to citizens under certain conditions. The main prerequisites for efficiency are the expected perception of technology, trust in the government’s actions, the expected efficiency and quality of electronic communications. The purpose of the research is to study the trends and problems of e-governance development in Ukraine on the basis of the concept of m-governance through the assessment of the usability of the mobile application of the government “Diia” (“Action”). This study is based on the concept of m-governance, a technocentric approach to quantifying the usability of mobile applications within the digital concept of Ukraine “Country in your smartphone”. Based on a survey of 800 users, the usability of the mobile application “Diia” was assessed. The article is based on a comparison of the practice of developed and developing countries. It has been revealed no differences in the effectiveness of the integration of the concept of m-governance. The results prove the importance of usability criteria in the use of mobile applications, but there is no connection between the socio-economic characteristics of users and usability. The study proves the importance of emotional components in the integration of the concept of m-governance: trust, perception, expectations of citizens. Integration strategy and tactics are important, as digital user skills and application specifications (visibility, user control and freedom, consistency and standards, error prevention, recognition, flexibility and efficiency of use, aesthetic and minimalist design, help users recognize, diagnose, and recover from errors, help and documentation). Both the government and citizens are responsible for the effectiveness of technological interaction solutions. The study proves that the government should ensure the formation of confidence in the effectiveness of technology, develop a strategy, tactics of integration based on best practices. On the other hand, citizens are responsible for their own technological readiness through an objective assessment of digital skills.